Rapid annealing-transformed, intense-red-emitting Eu-doped ZnGa2O4 nanoparticles with high colour purity, for very-high-resolution display applications. (November 2019) - Hebbar N, Deepak; Choudhari, K.S.; Pathak, Nimai; Shivashankar, S.A.; Kulkarni, Suresh D.
Graphical abstract: Highlights: Mere 15min Rapid Annealing(RA) produces intense red-emitting phosphor. 900°C RA of ZnGa1.99 Eu0.01 O4 yields 84% colour purity without grain growth. 8nm nanoparticles: well suited as pixels for very-high-resolution displays. Two life times obtained shows Eu 3+ on particle surface and within. RA could be explored for other important phosphors for LED and display. Abstract: Rapid annealing (RA), an eco-friendly, soft processing technique was employed to manipulate emission properties of nanocrystalline ZnGa1.99 Eu0.01 O4 . With RA processing that lasts only minutes, nanocrystals with weak emission were transformed into intense red-emitting phosphor. Effect of RA process parameters: temperature, duration, and cycling, on emission properties has been thoroughly studied. Compared to furnace annealing that usually lasts hours, RA, which involves simple and inexpensive apparatus, is shown to be very efficient and beneficial, as the total process time is only 15 min. This swift processing leads to enhanced quantum yield and higher colour purity (84%), without grain growth. Even after RA at 900 °C, crystallites measure ˜7-8 nm, suggesting that they might serve as pixels for very-high-resolution applications. Two PL-lifetimes obtained, imply Eu 3+ distribution (i) on the nanocrystal surface, (ii) within host-lattice (spinel gallate); the distribution changes gradually with RA. Judd-Ofelt analysis and spectroscopic analysis of the PL have been discussed in detail.